Carbon skeleton loaded platinum monatomic-cobalt nanoparticle catalyst, preparation method thereof and application of carbon skeleton loaded platinum monatomic-cobalt nanoparticle catalyst in electro-catalytic hydrogen evolution
By loading Co nanoparticles and platinum single atoms on the carbon framework, the OH adsorption capacity of Co nanoparticles and the synergistic effect of Pt single atoms is solved, and the activity of Pt-based catalysts is reduced and competitive adsorption is achieved during the catalytic hydrogen evolution reaction under alkaline conditions, thereby achieving efficient alkaline hydrogen evolution reaction.
Patent Information
- Application Number
- CN202411638934.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
When existing Pt-based catalysts catalyze hydrogen evolution reaction under alkaline conditions, Pt single atoms tend to aggregate to form clusters, resulting in a decrease in catalytic activity. At the same time, the competitive adsorption problem of OH* and H* leads to slow electrocatalytic kinetics.
ZIF-67@ZIF-8 precursor was prepared by epitaxial growth, and the carbon matrix containing Co nanoparticles was thermally deconstructed, and the Co nanoparticle size was regulated by tannin etching. Platinum single atoms were accurately bounded with Pt−N bonds within the carbon skeleton, and a cube-shaped carbon skeleton supported Pt single atom-Co nanoparticle catalyst was constructed.
The catalytic performance of the alkaline hydrogen evolution reaction is significantly improved, and the hydrogen generation rate and catalyst stability are improved through the OH adsorption capacity of Co nanoparticles and the synergistic effect of Pt single atoms.
Smart Images

Figure CN119753731A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis and energy conversion, and specifically relates to a carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst, a preparation method thereof, and an application in electrocatalytic hydrogen evolution to achieve efficient alkaline hydrogen evolution (HER). More specifically, the present invention prepares a double-encapsulated MOF precursor (ZIF-8@ZIF-67 NB) by epitaxial growth, and pyrolyzes it to construct a carbon matrix containing Co nanoparticles. In the preparation process of ZIF-67@ZIF-8, tannic acid with multiple phenolic hydroxyl groups can replace dimethylimidazole and form a stable complex with metal ions to regulate the MOF framework structure. By regulating the tannic acid treatment time (TA x -ZIF-67@ZIF-8 NB), the particle size of Co nanoparticles can be precisely controlled, and the single platinum atoms can be precisely confined within the carbon skeleton with Pt-N bonds to construct a cubic carbon skeleton-loaded Pt single atom-Co nanoparticle catalyst. This catalyst exhibits excellent catalytic performance in alkaline hydrogen evolution reaction and is expected to be widely used in water electrolysis hydrogen production technology. Background Art
[0002] Hydrogen evolution by water electrolysis has attracted extensive attention as an effective way to generate and store new energy using renewable energy. Pt-based catalysts are considered to be the best catalysts for catalyzing HER under alkaline conditions. However, the high price of Pt and its scarce reserves have caused people to worry about the cost of using large amounts of Pt catalysts. Pt-loaded catalysts have become an excellent alternative. However, due to the high activity of Pt single atoms, they are easy to aggregate to form clusters, resulting in reduced catalytic activity. At the same time, there is a problem of competitive adsorption of OH* and H* at a single active site in the HER reaction, resulting in slow electrocatalytic kinetics. Therefore, it is necessary to design dual-site catalysts such as Pt particles-Pt atoms to overcome the problem of competitive adsorption of OH* and H*.
[0003] Dual-site catalysts include homonuclear (such as Pd particles-Pd atoms) and heteronuclear catalysts (Ru particles-Pt atoms). Compared with homonuclear, heteronuclear catalysts are conducive to the identification of active sites. For this type of particle-single atom catalyst, selecting transition metal nanoparticles with moderate adsorption capacity for OH is not only beneficial to avoid the use of precious metals, but also can accelerate water splitting by adsorbing OH. Co nanoparticles have become suitable candidate materials due to their strong OH adsorption capacity. The HER performance of Co nanomaterials mainly depends on their lattice structure, size and surface properties. By rationally designing the size of Co nanomaterials, its adsorption strength for OH can be regulated, and then the synergistic effect with Co nanoparticles and Pt can be precisely controlled to enhance the HER activity of the catalyst. Summary of the invention
[0004] The present invention provides a carbon skeleton supported platinum single atom-cobalt nanoparticle catalyst and its preparation method and application in electrocatalytic hydrogen evolution. The present invention uses tannic acid etching to control the Co size in the "Co nanoparticle-Pt single atom" dual-site catalyst, aiming to achieve the synergistic effect of the two components by controlling the size of the Co particles and significantly improve the alkaline HER catalytic performance. Different Co nanoparticles have different effects on OH ad Suitable Co nanoparticles require less energy to decompose water and can enrich the local proton concentration around the Pt site by adsorbing OH, thereby significantly promoting the adsorption of protons on Pt single atoms and the generation of hydrogen.
[0005] The present invention is achieved by adopting the following technical scheme: a preparation method of a carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst, wherein a ZIF-67@ZIF-8 precursor is prepared by an epitaxial growth method, and the precursor is pyrolyzed to construct a carbon matrix containing Co nanoparticles; in the preparation process of ZIF-67@ZIF-8, the tannic acid treatment time is regulated to accurately control the size of the Co nanoparticles; at the same time, uniform N vacancies generated during the high-temperature pyrolysis process are conducive to the precise confinement of the Pt−N bond, thereby experimentally analyzing the atomic state distribution of Pt; and finally constructing a carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst.
[0006] Further, the following steps are included: (1) Preparation of ZIF-8@ZIF-67 precursor treated with tannic acid: Synthesis of ZIF-8 nanocubes ZIF-8 NB: 5 mL of aqueous solution containing 300 mg of zinc acetate dihydrate Zn(CH2COO)2 was slowly added to 5 mL of aqueous solution containing 1116 mg of dimethylimidazole and 0.8 mg of hexadecyltrimethylammonium bromide CTAB; the mixture was shaken for 10 s and allowed to stand at room temperature for 2 h; the obtained ZIF-8 NC was washed several times with ultrapure water and then dried in a drying oven; Synthesis of ZIF-67-coated ZIF-8 nanocubes ZIF-67@ZIF-8 NB: 72 mL ultrapure water was added to 360 mg of the synthesized ZIF8 nanocubes, and solution A was obtained after ultrasonic dispersion. Meanwhile, 456.3 mg of cobalt nitrate hexahydrate and 23.67 mg of CTAB were put into 16 mL ultrapure water, ultrasonically dispersed and added to solution A to obtain solution B. 7.134 g of dimethylimidazole was uniformly dispersed in 110 mL ultrapure water to obtain solution C, and then solution C was slowly added to solution B, stirred for 24 h, centrifuged and dried to obtain ZIF-67@ZIF-8 NB. Synthesis of tannic acid modified ZIF-67 coated ZIF-8 nanocubes TA x-ZIF-67@ZIF-8 NB: 600 mg of tannic acid was dispersed in 133 mL of ultrapure water to prepare a tannic acid solution under light-proof conditions. 400 mg of ZIF-67@ZIF-8NB was dispersed in a mixed solution of 200 mL of ultrapure water and 20 mL of ethanol, and then slowly added to the tannic acid solution. The tannic acid treatment time was adjusted to 0-16 h, and the corresponding material was named TA x -ZIF-67@ZIF-8 NB, where x is the duration of tannic acid treatment; (2) Preparation of TA x -ZIF-67@ZIF-8 NB-derived carbon TA x -ZIF-67@ZIF-8 NB-C: TA obtained in step (1) x -ZIF-67@ZIF-8 NB precursor was placed in a porcelain boat, and then placed in a tube furnace, heated to 920°C at a rate of 2°C / min, and kept warm for 180 min in an argon atmosphere; and then taken out after cooling to room temperature; (3) Preparation of Co nanoparticles-Pt single atom catalysts of different sizes nx -Pt1@C NB: 50 mg TA obtained in step (2) x -ZIF-67@ZIF-8 NB-C sample was dispersed in 10 mL ultrapure water and ultrasonically dispersed for 20 min to obtain a uniform suspension; 560 μL of 20 mg / mL chloroplatinic acid hexahydrate aqueous solution was slowly added; after stirring at 10-80 °C for 16 h, the suspension was centrifuged and separated; the precipitate was washed with ultrapure water and then dried under vacuum at 60 °C overnight to obtain Co nx -Pt1@C NB, where n refers to nanoparticles, x It is the duration of tannic acid treatment.
[0007] The present invention also provides a carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst Co prepared by the method. nx -Pt1@C NB.
[0008] The present invention also provides the carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst Co nx -Application of Pt1@C NB in electrocatalytic hydrogen evolution.
[0009] Furthermore, the carbon skeleton is loaded with platinum single atom-cobalt nanoparticle catalyst Co nx-Pt1@C NB dispersion was coated on the surface of carbon paper as the working electrode, carbon rod as the counter electrode, mercury / mercury oxide electrode as the reference electrode to form a three-electrode system for alkaline HER reaction. The catalyst was subjected to linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests using an electrochemical workstation to evaluate its electrocatalytic performance.
[0010] Furthermore, the specific method is as follows: 2.5 mg powdered Co nx -Pt1@C NB sample was dispersed in a mixed solution of 100 μL ethanol and 135 μL ultrapure water. After ultrasonic dispersion, 15 μL Nafion reagent was added to the mixed solution, and ultrasonic dispersion was continued for 1 h at a temperature of ≤20°C to prepare catalyst ink. Use a microinjector to drop 20 μL of ink onto a 0.5*0.5 cm carbon paper 10 times and dry it at room temperature to prepare a working electrode. A carbon rod was selected as the counter electrode, a mercury / mercury oxide electrode was selected as the reference electrode, and carbon paper coated with catalyst ink was selected as the working electrode to form a three-electrode system. The catalyst was tested by linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) using an electrochemical workstation to evaluate its electrocatalytic performance. First, the mercury / mercury oxide electrode was calibrated by reversible hydrogen electrode (RHE) in a high-purity H2-saturated 1 M KOH solution. Two Pt foils were used as the working electrode and the counter electrode, respectively, and mercury / mercury oxide was used as the reference electrode. The potential range was -0.7 to -1.1 V at 2 mV s -1 Cyclic voltammetry (CV) was performed at a scan rate of 1.5 % and the average of the two potentials with zero current was taken as the thermodynamic potential of the hydrogen electrode reaction. The RHE-calibrated CV results for mercury / mercuric oxide in 1 M KOH can be described as E ( vs. RHE) = E ( vs. Mercury / mercury oxide) +0.912 V; The three-electrode system was then placed in Ar-saturated 1 M KOH at −0.8 V to −1.25 V ( vs. The linear sweep voltammetry was performed at a rate of 5 mV s -1 Perform LSV test to detect Co nx -HER behavior of Pt1@C NB under alkaline conditions; the Tafel slope is determined by plotting the logarithm of the current density versus the overpotential (log |j|); The EIS measurements were performed at 10 5 Hz to 10 -2Hz frequency range, with an amplitude of 5 mV and at different -0.034 V ( vs. The impedance test is carried out under RHE potential; the solution resistance R can be obtained through the impedance spectrum s , then use E = E RHE -90%iR s To perform liquid resistance correction on the LSV curve; The electrochemically active surface area (ECSA) of the three-electrode system was determined by cyclic voltammetry: vs. RHE) at 20, 40, 60, 80, 100, and 120 mV -1 The CV test was performed at a scan rate of Δj / 2 = (j 阳极 -j 阴极 ) / 2 vs. scan rate, the slope is the electrochemical double layer capacitance (C dl ),j 阳极 and j 阴极 Respectively represents 0.217 V ( vs. The current density of the anodic and cathodic scans under RHE is calculated; ECSA is calculated based on the relationship between the electrochemical double layer capacitance and the capacitance per unit surface area; the formula is: ECSA = C dl / C s , where C s is the capacitance per unit surface area and is generally a known constant for a particular electrode material.
[0011] In the present invention, the precursor ZIF-67@ZIF-8 is etched by tannic acid and then pyrolyzed to construct a carbon matrix containing Co nanoparticles of different sizes. At the same time, Pt single atoms are precisely confined to the carbon skeleton by Pt-N bonds to synthesize nitrogen-doped carbon hollow nanocubes (Co nanoparticles of different sizes and Pt single atoms). nx -Pt1@C NB). Co nanoparticles react with OH ad The adsorption of Co is stronger, and less energy is required to decompose water. Co enriches the local proton concentration around the Pt site, thereby significantly promoting the adsorption of protons on Pt single atoms and the generation of hydrogen. The manifestation of this bifunctional catalytic effect effectively improves the overall catalytic efficiency of the alkaline hydrogen evolution reaction.
[0012] The present invention investigates the effect of tannic acid treatment time in the precursor on the Co nx-Pt1@C NB catalyst performance. It shows that the best alkaline HER catalytic activity is obtained when treated with tannic acid for an appropriate time. The structure shows uniformly distributed Co nanoparticles with a particle size of about 10 nm. This structure not only gives the material a large specific surface area, but also gives the material excellent conductivity and dispersibility, which significantly improves the HER performance of the prepared electrode material under alkaline conditions. Compared with the existing technology, the improvement in alkaline HER performance of this material is mainly attributed to its unique structural design. By precisely controlling the synergistic effect of Co nanoparticles and single-atom Pt, the material exhibits higher electrocatalytic activity, better stability and durability. This innovative design provides a new direction for the development of efficient electrocatalysts in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The samples treated with tannic acid for 4 h at different resolutions (Co n4 -Pt1@C NB) transmission electron microscopy image; the scales in the figure are: A, B are 10nm; C is 20nm, D is 50nm, E, F are 100nm; Figure 2 Calibrate the potential of the reference electrode against RHE; Figure 3 LSV curves (a) and Tafel (b) curves corresponding to samples treated with different tannic acid treatment times; Figure 4 The impedance diagrams of samples treated with tannic acid for different time periods at a potential of -965 mV (relative to saturated calomel electrode) are shown; Figure 5 a is the scanning rate of the sample without tannic acid treatment in 1 M KOH at different scanning rates (from 20 mV s -1 To 20 mV s -1 ) Cyclic voltammetry curve of the sample at 0.117−0.317 V (relative to saturated calomel electrode); Figure 5 b shows the samples treated with tannic acid for 4 h at different scan rates (from 20 mV s -1 To 20 mV s -1 ) Cyclic voltammetry curve of the sample at 0.117−0.317 V (relative to saturated calomel electrode); Figure 5 c is the calculated double layer capacitance current at 0.217 V (relative to saturated calomel electrode) as a function of scan rate. DETAILED DESCRIPTION In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0014] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0015] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0016] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.
[0017] 1. Carbon skeleton supported platinum single atom-cobalt nanoparticle catalyst Co nx Preparation of Pt1@C NBs (1) Preparation of tannic acid treated ZIF-8@ZIF-67 precursor Synthesis of ZIF-8 nanocubes (ZIF-8 NB): 5 mL of an aqueous solution containing 300 mg of zinc acetate dihydrate (Zn(CH2COO)2) was slowly added to 5 mL of an aqueous solution containing 1116 mg of dimethylimidazole and 0.8 mg of hexadecyltrimethylammonium bromide (CTAB). The mixture was shaken for 10 s and allowed to stand at room temperature for 2 h. The resulting ZIF-8 NCs were washed several times with ultrapure water and dried in a drying oven.
[0018] Synthesis of ZIF-67-coated ZIF-8 nanocubes (ZIF-67@ZIF-8 NB): 72 mL ultrapure water was added to 360 mg of ZIF-8, and solution A was obtained after ultrasonic dispersion. Meanwhile, 456.3 mg of cobalt nitrate hexahydrate and 23.67 mg of CTAB were placed in 16 mL ultrapure water, ultrasonically dispersed and added to solution A to obtain solution B. 7.134 g of dimethylimidazole was uniformly dispersed in 110 mL ultrapure water to obtain solution C, which was then slowly added to solution B, stirred for 24 h, centrifuged and dried to obtain ZIF-67@ZIF-8 NB.
[0019] Synthesis of tannic acid-modified ZIF-67-coated ZIF-8 nanocubes (TA x -ZIF-67@ZIF-8 NB): 600 mg of tannic acid was dispersed in 133 mL of ultrapure water to prepare a tannic acid solution (due to the characteristic of tannic acid decomposing under light, the lights were turned off during the weighing process, and the beaker containing the tannic acid solution was wrapped with aluminum foil or tin foil to avoid light), 400 mg of ZIF-67@ZIF-8 NB was dispersed in a mixed solution of 200 mL of ultrapure water and 20 mL of ethanol, and slowly added to the tannic acid solution. Since the main variable of this experiment was the tannic acid treatment time (0-16 h), the corresponding material was named TA x -ZIF-67@ZIF-8 NB, where x The treatment time of tannic acid was 0, 1, 4, 8, and 16 h. The obtained materials were named TA0-ZIF-67@ZIF-8 NB, TA1-ZIF-67@ZIF-8 NB, TA4-ZIF-67@ZIF-8 NB, TA8-ZIF-67@ZIF-8 NB, TA 16 -ZIF-67@ZIF-8 NB; (2) Preparation of TA x -ZIF-67@ZIF-8 NB-derived carbon (TA x -ZIF-67@ZIF-8 NB-C): TA obtained in step (1) x -ZIF-67@ZIF-8 NB was placed in a porcelain boat, and the prepared porcelain boats were placed in a tube furnace, heated to 920°C at a rate of 2°C / min, and kept warm for 180 min in an argon atmosphere. After cooling to room temperature, the TA was taken out. x -ZIF-67@ZIF-8NB-C.
[0020] (3) Preparation of Co nanoparticle-Pt single atom catalyst (Co nx -Pt1@C NB): The TA obtained in step (2) x -ZIF-67@ZIF-8 NB-C (50 mg) sample was dispersed in 10 mL ultrapure water and then ultrasonically dispersed for 20 min to obtain a uniform suspension. Next, 560 μL of chloroplatinic acid hexahydrate aqueous solution (20 mg / mL) was slowly added. After stirring at 10-80 °C for 16 h, the suspension was centrifuged. The precipitate was washed several times with ultrapure water and then dried overnight under vacuum at 60 °C.
[0021] Figure 1 The sample treated with tannic acid for 4 h (Co n4 -Pt1@C NB) transmission electron microscopy image, Con4 -Pt1@C NB has a smooth surface, regular core-shell structure, and a regular hexahedral structure. There are large Co nanoparticles on the surface and they are evenly distributed. The particle size is about 10 nm. At the same time, it can be seen that the particles are wrapped by a thin carbon layer, which is beneficial to protect them from corrosion during the electrochemical process, which improves the Co n4 -Corrosion resistance and stability of Pt1@C NB catalyst.
[0022] 2. HER electrochemical performance test under alkaline conditions 2.5 mg of powdered sample was dispersed in a mixed solution of 100 μL ethanol and 135 μL ultrapure water. After ultrasonic dispersion, 15 μL Nafion reagent was added to the mixed solution, and ultrasonic dispersion was continued for 1 h at a temperature below 20 °C to prepare catalyst ink. 20 μL of ink was repeatedly dripped onto 0.5*0.5 cm carbon paper 10 times using a microinjector and dried at room temperature.
[0023] A carbon rod was selected as the counter electrode, a mercury / mercury oxide electrode was selected as the reference electrode, and carbon paper coated with catalyst ink was selected as the working electrode to form a three-electrode system. The catalyst was subjected to linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests using an electrochemical workstation to evaluate its electrocatalytic performance.
[0024] The mercury / mercury oxide electrode was first calibrated with a reversible hydrogen electrode (RHE) in a high-purity H2-saturated 1 M KOH solution using two Pt foils as the working electrode and the counter electrode, respectively, and mercury / mercury oxide as the reference electrode. -1 Cyclic voltammetry (CV) was performed at a scan rate of 1.5 volts and the average of the two potentials with zero current was taken as the thermodynamic potential of the hydrogen electrode reaction. The RHE-calibrated CV results for mercury / mercury oxide in 1 M KOH can be described as E ( vs. RHE) = E ( vs. Mercury / mercury oxide) +0.912 V. Figure 2 The potential calibration value of the reference electrode to RHE can be obtained.
[0025] The three-electrode system was then placed in Ar-saturated 1 M KOH at −0.8 V to −1.25 V ( vs. The linear sweep voltammetry was performed at a rate of 5 mV s -1 Perform LSV test to detect Co nx-HER behavior of Pt1@C NB under alkaline conditions. The Tafel slope is determined by plotting the current density versus the logarithm of the overpotential (log |j|).
[0026] The EIS measurements were performed at 10 5 Hz to 10 -2 Hz frequency range, with an amplitude of 5 mV and at different -0.034 V ( vs. The impedance test is carried out under RHE potential. The solution resistance R can be obtained through the impedance spectrum. s , then use E = E RHE -90%iR s To perform liquid resistance correction on the LSV curve.
[0027] The electrochemically active surface area (ECSA) of the three-electrode system was determined by cyclic voltammetry. vs. RHE) at 20, 40, 60, 80, 100, and 120 mV -1 CV test was performed at a scan rate of Δj / 2 = (j 阳极 -j 阴极 ) / 2 vs. scan rate, the slope is the electrochemical double layer capacitance (C dl ),j 阳极 and j 阴极 Respectively represents 0.217 V ( vs. The current density of the anodic and cathodic scans under RHE.
[0028] ECSA is calculated by the relationship between electrochemical double layer capacitance and unit surface area capacitance. The formula is: ECSA =C dl / C s , where C s is the capacitance per unit surface area and is generally a known constant for a particular electrode material.
[0029] 3. Actual sample detection: First, the synthesized carbon skeleton is loaded with platinum single atom-cobalt nanoparticle catalyst Co according to the method shown in step 2. nx -Pt1@C NB was uniformly coated on carbon paper to prepare a working electrode for electrochemical testing. Then, an electrochemical workstation was used to measure the hydrogen evolution reaction (HER) activity of the sample under alkaline conditions in a three-electrode system. LSV, EIS and CV tests were performed in sequence according to the same electrochemical test method as step 2. According to the method shown in step 2, according to the R obtained in EIS s The LSV curves were corrected for liquid resistance and the electrochemical active surface area of the material was calculated.
[0030] The LSV curve is corrected for liquid resistance and the Figure 3 ,from Figure 3 The current density in a is 10 mA cm -2 The overpotentials of the samples treated with tannic acid for 0 h, 1 h, 4 h, 8 h, and 16 h were 0.058 V, 0.037 V, 0.033 V, 0.037 V, and 0.045 V, respectively. It can be seen that the overpotentials of the samples treated with tannic acid for 4 h at 10 mA cm -2 It has the lowest overpotential, indicating that it has the strongest catalytic activity.
[0031] from Figure 3 From b, we can see that the Tafel slopes of the samples treated with tannic acid for 0 h, 1 h, 4 h, 8 h, and 16 h are 85.5 mV dec, respectively. -1 , 65.7 mV dec -1 , 57.1 mV dec -1 , 58.9 mV dec -1 , 64.9 mV dec -1 , it can be seen that the tannic acid treatment time of 4 h has the lowest Tafel slope, indicating that it has the fastest catalytic kinetics.
[0032] As the treatment time increases, its catalytic activity first increases and then decreases, indicating that only Co nanoparticles of appropriate size can achieve optimal synergistic catalysis with Pt single atoms. If the Co nanoparticles are too small, the adsorption of OH* will be too weak, resulting in limited coverage of hydrogen protons on the Pt surface. If the Co nanoparticles are too large, the adsorption of OH* will be too strong and OH* cannot be dissociated, resulting in an inability to continuously supply hydrogen protons on the Pt surface.
[0033] from Figure 4 The EIS spectrum shows that the charge transfer resistance of the sample treated with tannic acid for 4 h is much smaller than that of the samples treated with other tannic acid times, which proves that Co n4 -Pt1@C NBs have small charge transfer resistance and fast electron transfer speed, which leads to fast HER kinetics, especially in alkaline electrolytes.
[0034] from Figure 5 It can be seen that the double layer capacitance of the sample without tannic acid treatment and the sample treated with tannic acid for 4 h is 28.3 mF cm -2 and 34.0 mF cm -2 The sample treated with tannic acid for 4 h has a larger double-layer capacitance, indicating that the treatment with tannic acid increases the n4 -The active specific surface area of Pt1@C NB catalyst is an important factor in improving the electrocatalytic HER activity.
[0035] Based on the above test results, it can be seen that the Co nanoparticle-Pt single atom catalyst constructed in the present invention exhibits excellent electrocatalytic HER activity under alkaline conditions. This catalyst not only effectively improves the hydrogen evolution reaction rate by finely regulating the synergistic effect of Co nanoparticles and Pt single atoms, but also exhibits a lower Tafel slope, further proving its efficient catalytic performance in alkaline media. In short, this new catalyst provides an effective way to improve the efficiency of alkaline electrocatalytic HER and has potential application prospects.
[0036] In the present invention, the precursor ZIF-67@ZIF-8 is etched by tannic acid and then pyrolyzed to construct a carbon matrix containing Co nanoparticles. At the same time, Pt single atoms are precisely confined to the carbon skeleton by Pt-N bonds to synthesize nitrogen-doped carbon hollow nanocubes (Co nanoparticles and Pt single atoms). nx -Pt1@C NB).
[0037] The present invention investigates the effect of tannic acid treatment time in the precursor on the Co nx -Pt1@C NB catalyst performance. It shows that the best alkaline HER catalytic activity is obtained when treated with tannic acid for an appropriate time. The structure shows uniformly distributed Co nanoparticles with a particle size of about 10 nm. This structure not only gives the material a large specific surface area, but also gives the material excellent conductivity and dispersibility, which significantly improves the HER performance of the prepared electrode material under alkaline conditions. Compared with the existing technology, the improvement in alkaline HER performance of this material is mainly attributed to its unique structural design. By precisely controlling the synergistic effect of Co nanoparticles and single-atom Pt, the material exhibits higher electrocatalytic activity, better stability and durability. This innovative design provides a new direction for the development of efficient electrocatalysts in the future.
[0038] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst, characterized in that: The ZIF-67@ZIF-8 precursor was prepared by epitaxial growth and pyrolyzed to construct a carbon matrix containing Co nanoparticles. During the preparation of ZIF-67@ZIF-8, the tannic acid treatment time was adjusted to precisely control the size of the Co nanoparticles. At the same time, the uniform N vacancies generated during the high-temperature pyrolysis process were conducive to the precise confinement of the Pt-N bond, thereby experimentally determining the atomic state distribution of Pt. Finally, a carbon skeleton-loaded platinum single atom-cobalt nanoparticle catalyst was constructed.
2. The preparation method according to claim 1, characterized in that: The steps include: (1) Preparation of ZIF-8@ZIF-67 precursor treated with tannic acid: Synthesis of ZIF-8 nanocubes ZIF-8 NB: 5 mL of aqueous solution containing 300 mg of zinc acetate dihydrate Zn(CH2COO)2 was slowly added to 5 mL of aqueous solution containing 1116 mg of dimethylimidazole and 0.8 mg of hexadecyltrimethylammonium bromide CTAB; the mixture was shaken for 10 s and allowed to stand at room temperature for 2 h; the obtained ZIF-8 NC was washed several times with ultrapure water and then dried in a drying oven; Synthesis of ZIF-67-coated ZIF-8 nanocubes ZIF-67@ZIF-8 NB: 72 mL ultrapure water was added to 360 mg of the synthesized ZIF8 nanocubes, and solution A was obtained after ultrasonic dispersion. Meanwhile, 456.3 mg of cobalt nitrate hexahydrate and 23.67 mg of CTAB were put into 16 mL ultrapure water, ultrasonically dispersed and added to solution A to obtain solution B. 7.134 g of dimethylimidazole was uniformly dispersed in 110 mL ultrapure water to obtain solution C, and then solution C was slowly added to solution B, stirred for 24 h, centrifuged and dried to obtain ZIF-67@ZIF-8 NB. Synthesis of tannic acid modified ZIF-67 coated ZIF-8 nanocubes TA x -ZIF-67@ZIF-8 NB: 600 mg of tannic acid was dispersed in 133 mL of ultrapure water to prepare a tannic acid solution under light-protected conditions. 400 mg of ZIF-67@ZIF-8 NB was dispersed in a mixed solution of 200 mL of ultrapure water and 20 mL of ethanol, and then slowly added to the tannic acid solution. The tannic acid treatment time was adjusted to 0-16 h, and the corresponding material was named TA x -ZIF-67@ZIF-8 NB, where x is the duration of tannic acid treatment; (2) Preparation of TA x -ZIF-67@ZIF-8 NB-derived carbon TA x -ZIF-67@ZIF-8 NB-C: TA obtained in step (1) x -ZIF-67@ZIF-8 NB precursor was placed in a porcelain boat, and then placed in a tube furnace, heated to 920°C at a rate of 2°C / min, and kept warm for 180 min in an argon atmosphere; and then taken out after cooling to room temperature; (3) Preparation of Co nanoparticles-Pt single atom catalysts of different sizes nx -Pt1@C NB: 50 mg TA obtained in step (2) x -ZIF-67@ZIF-8 NB-C sample was dispersed in 10 mL ultrapure water and ultrasonically dispersed for 20 min to obtain a uniform suspension; 560 μL of 20 mg / mL chloroplatinic acid hexahydrate aqueous solution was slowly added; after stirring at 10-80 °C for 16 h, the suspension was centrifuged and separated; the precipitate was washed with ultrapure water and then dried under vacuum at 60 °C overnight to obtain Co nx -Pt1@C NB, where n refers to nanoparticles, x It is the duration of tannic acid treatment.
3. The preparation method according to claim 2, characterized in that: The tannin treatment time was 4 h, and the obtained Co nanoparticle-Pt single atom catalyst was Co n4 -Pt1@C NB.
4. A carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst Co prepared by the method of any one of claims 1 to 3 nx -Pt1@C NB.
5. The carbon skeleton-supported platinum single atom-cobalt nanoparticle catalyst Co according to claim 4 nx -Application of Pt1@C NB in electrocatalytic hydrogen evolution.
6. The use according to claim 5, characterized in that: The carbon framework is loaded with platinum single atom-cobalt nanoparticle catalyst Co nx -Pt1@C NB dispersion was coated on the surface of carbon paper as the working electrode, carbon rod as the counter electrode, mercury / mercury oxide electrode as the reference electrode to form a three-electrode system for alkaline HER reaction. The catalyst was subjected to linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests using an electrochemical workstation to evaluate its electrocatalytic performance.
7. The use according to claim 6, characterized in that: The specific method is: 2.5 mg powdered Co nx -Pt1@C NB sample was dispersed in a mixed solution of 100 μL ethanol and 135 μL ultrapure water. After ultrasonic dispersion, 15 μL Nafion reagent was added to the mixed solution, and ultrasonic dispersion was continued for 1 h at a temperature of ≤20°C to prepare catalyst ink. Use a microinjector to drop 20 μL of ink onto a 0.5*0.5 cm carbon paper 10 times and dry it at room temperature to prepare a working electrode. A carbon rod was selected as the counter electrode, a mercury / mercury oxide electrode was selected as the reference electrode, and carbon paper coated with catalyst ink was selected as the working electrode to form a three-electrode system. The catalyst was tested by linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) using an electrochemical workstation to evaluate its electrocatalytic performance. First, the mercury / mercury oxide electrode was calibrated by reversible hydrogen electrode (RHE) in a high-purity H2-saturated 1 M KOH solution. Two Pt foils were used as the working electrode and the counter electrode, respectively, and mercury / mercury oxide was used as the reference electrode. The potential range was -0.7 to -1.1 V at 2 mV s -1 Cyclic voltammetry (CV) was performed at a scan rate of 1.5 % and the average of the two potentials with zero current was taken as the thermodynamic potential of the hydrogen electrode reaction. The RHE-calibrated CV results for mercury / mercuric oxide in 1 M KOH can be described as E ( vs. RHE) = E ( vs. Mercury / mercury oxide) +0.912 V; The three-electrode system was then placed in Ar-saturated 1 M KOH at −0.8 V to −1.25 V ( vs. The linear sweep voltammetry was performed at a rate of 5 mV s -1 Perform LSV test to detect Co nx -HER behavior of Pt1@C NB under alkaline conditions; the Tafel slope is determined by plotting the logarithm of the current density versus the overpotential (log |j|); The EIS measurements were performed at 10 5 Hz to 10 -2 Hz frequency range, with an amplitude of 5 mV and at different -0.034 V ( vs. The impedance test is performed under RHE potential; the solution resistance R can be obtained through the impedance spectrum s , then use E = E RHE -90%iR s To perform liquid resistance correction on the LSV curve; The electrochemically active surface area (ECSA) of the three-electrode system was determined by cyclic voltammetry: vs. RHE) at 20, 40, 60, 80, 100, and 120 mV -1 The CV test was performed at a scan rate of Δj / 2 = (j 阳极 -j 阴极 ) / 2 vs. scan rate, the slope is the electrochemical double layer capacitance (C dl ),j 阳极 and j 阴极 Respectively represents 0.217 V ( vs. The current density of the anodic and cathodic scans under RHE is calculated; ECSA is calculated based on the relationship between the electrochemical double layer capacitance and the capacitance per unit surface area; the formula is: ECSA = C dl / C s , where C s is the capacitance per unit surface area and is generally a known constant for a particular electrode material.
Citation Information
Patent Citations
ZIF-67 template method for preparing cobalt-platinum core-shell particle / porous carbon composite material and catalytic application of composite material in cathode of fuel cell
CN106328960A
Cited By
Method for determining specific surface area of NFPP material based on cyclic voltammetry and application thereof
CN120507262A
Metal-organic framework derived gradient composite electrode with high selectivity as well as preparation method and application of metal-organic framework derived gradient composite electrode
CN122091608A
Porous carbon supported metal monatomic-metal sub-nano cluster synergistic catalyst as well as preparation method and application thereof
CN122382605A